Penyalahgunaan Wewenang Ditinjau Berdasarkan Hukum Administrasi Negara : Studi Kasus Nomor. 188.45/512/KPTS-BPT-2018 Tentang Pemberhentian Karena Melakukan Tindak Pidana Kejahatan Jabatan Atau Tindak Pidana Kejahatan - Margaret Pangaribuan; Ester Simanjuntak; Feby Adelia Parhusip; Muhammad Rifai; Berliana Sianturi; Taufiq Rahmadhan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The case of dishonorable dismissal for committing a criminal act of office crime shows a significant problem in government governance. This case developed from the Plaintiff being a level III civil servant based on the governor's decree, and then being appointed Secretary of the District DPKD. Based on the regent's decision, Sijunjung was placed in the BPKD functional position. Then the plaintiff was dishonorably dismissed because he was involved in a corruption case and was also deemed to have violated Pancasila and the 1945 Republic of Indonesia Constitution. has permanent legal force. In this case, several functions of state administrative law in creating good governance are really needed, including normative functions, instrumental functions and legal guarantee functions, all three of which are part of the application to create a clean government, in accordance with the principles of the rule of law.